Overexpression of chemokine receptor CXCR2 and ligand CXCL7 in liver metastases from colon cancer is correlated to shorter disease‐free and overall survival. Issue 3 (5th March 2015) - Desurmont, Thibault; Skrypek, Nicolas; Duhamel, Alain; Jonckheere, Nicolas; Millet, Guillaume; Leteurtre, Emmanuelle; Gosset, Pierre; Duchene, Belinda; Ramdane, Nassima; Hebbar, Mohamed; Van Seuningen, Isabelle; Pruvot, François‐René; et al.
Abstract : Our aim was to analyze the potential role of chemokine receptors CXCR2 and CXCR4 signalling pathways in liver metastatic colorectal cancer (CRC) relapse. CXCR2, CXCR4, and their chemokine ligands were evaluated in liver metastases of colorectal cancer in order to study their correlation with overall and disease‐free survival of patients having received, or not received, a neoadjuvant chemotherapy regimen. Quantitative RT‐PCR and CXCR2 immunohistochemical staining were carried out using CRC liver metastasis samples. Expression levels of CXCR2, CXCR4, and their ligands were statistically analyzed according to treatment with neoadjuvant chemotherapy and patients' outcome. CXCR2 and CXCL7 overexpression are correlated to shorter overall and disease‐free survival. By multivariate analysis, CXCR2 and CXCL7 expressions are independent factors of overall and disease‐free survival. Neoadjuvant chemotherapy increases significantly the expression of CXCR2: treated group 1.89 (0.02–50.92) vs 0.55 (0.07–3.22), P  = 0.016. CXCL7 was overexpressed close to significance, 0.40 (0.00–7.85) vs 0.15 (0.01–7.88), P  = 0.12. We show the involvement of CXCL7/CXCR2 signalling pathways as a predictive factor of poor outcome in metastatic CRC. 5‐Fluorouracil‐based chemotherapy regimens increase the expression of these genes in liver metastasis, providing one explanation for aggressiveness of relapsed drug‐resistant tumors. Selective blockage of CXCR2/CXCL7 signalling pathways could provide new potential therapeutic opportunities. Abstract : Univariate and multivariate analysis show that CXCR2 and CXCL7 are independent factors of overall and disease‐free survivals. CXCR2 and CXCL7 expression are increased in metastatic liver tissue of colorectal adenocarcinoma treated with 5‐FU based neoadjuvant chemotherapy with or without bevacizumab.